2018
DOI: 10.1111/cod.13118
|View full text |Cite
|
Sign up to set email alerts
|

European photopatch test baseline series: A 3‐year experience

Abstract: We present the largest clinical experience with the European photopatch test baseline series hitherto reported. The results are similar to those underlying the above consensus process, reaffirming the usefulness of this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
5
25
0
3
Order By: Relevance
“…Less than 0.18 mW/cm 2 of solar UVB at 310 nm can reach the blood vessels, and extremely long exposure times would be needed to cause any significant direct degradation of serum folate. 6 This finding is in agreement with clinical observations of patients with skin diseases treated with high UVB doses. 2 Given the limited skin penetration capacity of UVB, UVA may theoretically be of greater importance with regard to blood folate degradation.…”
Section: Doi: 101111/jdv16418supporting
confidence: 90%
See 3 more Smart Citations
“…Less than 0.18 mW/cm 2 of solar UVB at 310 nm can reach the blood vessels, and extremely long exposure times would be needed to cause any significant direct degradation of serum folate. 6 This finding is in agreement with clinical observations of patients with skin diseases treated with high UVB doses. 2 Given the limited skin penetration capacity of UVB, UVA may theoretically be of greater importance with regard to blood folate degradation.…”
Section: Doi: 101111/jdv16418supporting
confidence: 90%
“…5 Although UVA can penetrate much deeper into the skin, thus reaching more blood vessels than UVB, there is no convincing evidence of decreased folate levels after UVA exposure. [5][6][7] Investigations using NB-UVB showed controversial results, potentially explained by dosedependent degradation of folate, different assay methodology and study populations. 1,6,7 However, the research group of Moan 6 showed that direct photodegradation due to UVB is unlikely to occur.…”
Section: Doi: 101111/jdv16418mentioning
confidence: 99%
See 2 more Smart Citations
“…In some of the most recent multicentre photopatch studies, no case was reported. 3,8,9 UV filters are not contained in the baseline series or the cosmetic series. However, the use of creams for daily use that have UV absorbers in their composition is increasing.…”
Section: Case Reportmentioning
confidence: 99%